Study of Simultaneous Equation and Partial Simultaneous Equation Methods for the Spectrophotometric Estimation of Rosiglitazone Maleate and Glimepiride in Tablets - Jain, Rupshee; K. Kashaw, Sushil (Asian Journal of Chemistry, 2010)
Two new, simple, sensitive, accurate and reproducible spectrophotometric methods were developed for the simultaneous estimation of rosiglitazone maleate and glimepiride in combine dosage form. The methods employed are simultaneous equation method and partial simultaneous equation method. Method I employed generation and solving simultaneous equations using 248.5 and 228.5 nm as two analytical wavelengths and method II employed 312 and 228.5 nm as λ3 and λ2. Both drugs obeyed Beer's law in the concentration ranges of 2 to 16 μg/mL. Statistical analysis and recovery studies validated the method. The method is found to be rapid, precise and accurate and can easily be employed in the laboratory for routine estimation of drugs.